2013
DOI: 10.1183/09031936.00117213
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis transmission between foreign- and native-born populations in the EU/EEA: a systematic review

Abstract: Tuberculosis (TB) control programmes of many low TB incidence countries of the European Union/European Economic Area (EU/EEA) perceive challenges in controlling TB due to high numbers of TB in migrants from high-incidence countries.To assess the extent of TB transmission from the foreign-born to the native-born population, we quantitatively investigated the dynamics of TB transmission between these populations in the EU/EEA, using published molecular epidemiological studies. We searched PubMed and EMBASE datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 45 publications
(90 reference statements)
6
50
0
5
Order By: Relevance
“…Molecular epidemiology studies based on IS6110 restriction fragment length polymorphism (RFLP) indicated that during 1994 to 2005, on average, 2 nonimmigrants and 13 immigrants per year developed the disease as a result of infection within the country by imported Mycobacterium tuberculosis (Mtb) (2). Similar studies within the European Union/European Economic Area countries found that the TB incidence in a foreign-born population did not significantly affect the incidence of TB among the native population (2)(3)(4). However, these studies were based on RFLP, and the ability of this method to distinguish cases based on genetic homogeneity is limited.…”
mentioning
confidence: 50%
“…Molecular epidemiology studies based on IS6110 restriction fragment length polymorphism (RFLP) indicated that during 1994 to 2005, on average, 2 nonimmigrants and 13 immigrants per year developed the disease as a result of infection within the country by imported Mycobacterium tuberculosis (Mtb) (2). Similar studies within the European Union/European Economic Area countries found that the TB incidence in a foreign-born population did not significantly affect the incidence of TB among the native population (2)(3)(4). However, these studies were based on RFLP, and the ability of this method to distinguish cases based on genetic homogeneity is limited.…”
mentioning
confidence: 50%
“…In England, too, clusters often consisted of patients of multiple ethnicities and both homeless and nonhomeless populations (435). The aspect of transmission from immigrant to native populations in European Union/European Economic Area (EEA) countries was recently systematically reviewed (447). This review showed that the proportions of all studied TB cases that result from recent transmission within mixed (immigrant/native) clusters varied greatly between studies, from 0% to 34%; this proportion was Ͻ15% in 11 of the 15 studies analyzed (447).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
“…The aspect of transmission from immigrant to native populations in European Union/European Economic Area (EEA) countries was recently systematically reviewed (447). This review showed that the proportions of all studied TB cases that result from recent transmission within mixed (immigrant/native) clusters varied greatly between studies, from 0% to 34%; this proportion was Ͻ15% in 11 of the 15 studies analyzed (447). However, in the European Union/EEA, foreign-born patients are less likely to belong to a cluster than are native-born patients, and those authors conclude that TB in foreign-born populations has no significant impact on TB in the native European Union/EEA population (447).…”
Section: Applications Of Strain Typing To M Tuberculosis Complex Isomentioning
confidence: 99%
“…The sensitivity and specificity of CXR vary from 86-97% to 75-89%, respectively, and according to the criteria of imaging interpretation. CXR alone does not detect extrapulmonary TB (EPTB) which is increasing in comparison to pulmonary TB, especially in low-burden and high immigrant receiving countries [26], and in HIV-positive persons that have higher rates of EPTB compared with those who are HIV-negative.…”
Section: Screening Practices Among Adultsmentioning
confidence: 99%